Students’ Perceptions of Digital Audio Platforms in Supporting English Language Learning: An EF Context - Muhammad Gibran Ramadhan; Ratih Novita Sari (Universitas Islam Negeri Palopo, 2026)
This study investigates Grade 11 students’ perceptions of using digital audio platforms, particularly Spotify audiobooks, to support English language learning in an EFL context. Grounded in Mobile-Assisted Language Learning (MALL), the study focuses on learner autonomy, authentic listening exposure, and self-regulated listening strategies. Using a qualitative descriptive design, data were collected through open-ended questionnaires with 31 students, semi-structured interviews with 10 selected participants, and one classroom observation involving 31 students. The findings show that students perceived Spotify audiobooks as useful, flexible, and motivating because they allowed access to English input beyond the classroom and supported self-paced listening. Students also perceived fluent/authentic English audio as helpful for pronunciation awareness, listening familiarity, and vocabulary noticing. However, linguistic and technical barriers, such as speech speed, unfamiliar accents, vocabulary density, internet access, advertisements, and premium limitations, affected their learning experience. Students responded through repeated listening, playback adjustment, lyrics or transcripts, word searches, peer discussion, and preparation before learning. This study contributes to MALL-based EFL listening research by showing how Spotify audiobooks support perceived learning through autonomy, authentic exposure, teacher mediation, and coping strategies.